2005
DOI: 10.1016/j.febslet.2005.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of the metallochaperone Hah1 in its apo and Cu(I)‐loaded states: Role of the conserved residue M10

Abstract: Molecular dynamics simulations were performed on both apo and copper forms of the human copper chaperone, Hah1. Wild-type Hah1 and a methionine (M10) to serine mutant were investigated. We have evidenced the central role of residue M10 in stabilizing the hydrophobic core of Hah1 as well as the internal structure of the metal-binding site. When copper(I) is bound, the mobility of Hah1 is reduced whereas mutation of M10 implies a drastic increase of the mobility of apoHah1, stressing the importance of this highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…However, the small Ala10 side chain allows for fewer contacts than WT, extending to only Leu35 and Lys38, explaining the increased backbone dynamics in this region. We note that greater structural changes in apo versus holo forms because of the absence of Met10 was earlier reported for an Atox1 Met10Ser mutant on the basis of 5 ns MD simulations (25).…”
Section: Resultsmentioning
confidence: 72%
“…However, the small Ala10 side chain allows for fewer contacts than WT, extending to only Leu35 and Lys38, explaining the increased backbone dynamics in this region. We note that greater structural changes in apo versus holo forms because of the absence of Met10 was earlier reported for an Atox1 Met10Ser mutant on the basis of 5 ns MD simulations (25).…”
Section: Resultsmentioning
confidence: 72%
“…The best 30 structures of the DYANA family were then subjected to restrained energy minimization with AMBER 8.0 (39). The force-field parameters for the metal ions were adapted from similar systems (40,41). The statistical analysis of the restrained energy minimization family of apoHSco1, Cu(I)HSco1, and Ni(II)HSco1 structures are reported, respectively, in Tables 5, 6, and 7, which are published as supporting information on the PNAS web site.…”
Section: Methodsmentioning
confidence: 99%
“…However, the exact cause of this enhancement in both rate and extent of transfer varies between the two mutants. Previous molecular dynamics (MD) simulations of Met 10 Ser Atox1 indicated that Met-10 is essential for protein rigidity and for positioning the cysteines in proper orientation for Cu uptake (22). Greater flexibility may help to explain the almost 10-fold greater rate of Atox1 dissociation from the Met 10 Ala Atox1-Cu-BCA complex (k 2 ) compared to wild-type protein.…”
Section: Discussionmentioning
confidence: 99%
“…Although the methionine in the first position of the MXCXXC motif is conserved in all organisms, it is not directly involved in metal ligation (13). Instead, it has been proposed to act as a tether that modulates copper-binding loop structure (13,22).…”
mentioning
confidence: 99%